2020
DOI: 10.1101/2020.02.26.20026971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Features of COVID-19-Related Liver Damage

Abstract: BACKGROUND: A recent outbreak of SARS-CoV-2 infection occurs mainly in China,with rapidly increasing the number of cases (namely . Abnormal liver functions are frequently present in these patients, here we aimed to clarify the clinical features of COVID-19-related liver damage to provide some references for the clinical treatment. A total of 148 cases were analyzed for clinical features, laboratory parameters (including liver function tests), medications and the length of stay. FINDINGS:Of 148 confirmed SARS-C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
3
11

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(197 citation statements)
references
References 22 publications
4
179
3
11
Order By: Relevance
“…It's suggested that bile duct epithelial cells may play a key role in immunoreaction. However, clinical data from two researches showed that the bile duct injury related indexes alkaline phosphatase, gamma-glutamyl transpeptidase and total bilirubin did not increase significantly 10,14 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It's suggested that bile duct epithelial cells may play a key role in immunoreaction. However, clinical data from two researches showed that the bile duct injury related indexes alkaline phosphatase, gamma-glutamyl transpeptidase and total bilirubin did not increase significantly 10,14 .…”
Section: Discussionmentioning
confidence: 96%
“…Despite atypical pneumonia as the primary symptom, liver dysfunction has also been observed in many clinical cases [7][8][9] , indicating a possibility for the patients with COVID-19 may cause hepatic injury. Except that part of patients receiving lopinavir/ritonavir during hospitalization, which can cause drug-induced hepatic injury 10 , the underlying mechanisms for hepatic injury in patients with COVID-19 are still unclear. And there are few of clinical research regarding on this issue and it remains controversial now.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, published case studies reporting clinical features of patients with COVID-19 have shown that they may develop different degrees of liver dysfunction (summarized in Table 1). In these studies, the incidence of liver injury ranged from 14.8% to 78%, mainly presenting with abnormal levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) accompanied by slightly elevated bilirubin levels [8][9][10][11][12][13][14][15][16][17][18][19]. A deeper look at available data shows higher rates of abnormal levels in severe COVID-19, as high as 78% in one study [18].…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…Importantly, drug-induced liver injury during COVID-19 treatment should be carefully investigated. It might be caused by antiviral medications (lopinavir/ritonavir), antipyretics (acetaminophen), antibiotics (macrolides, quinolones) or steroids [31]. In a paper describing the first 12 patients with COVID-19 in the United States (U.S.), the three hospitalized patients, who received remdesivir at the time of clinical worsening, reported elevated liver enzymes [32].…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…90,91 However, clinical effectiveness remains unproven, and providers should be cognizant of the known side effect profile for this medication and monitor for hepatotoxicity, hyperglycemia, and arrythmias. 92 An ongoing clinical trial is comparing patients randomized to lopinavir/ritonavir and the viral fusion inhibitor arbidol (trial No. NCT04252885).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%